2017
DOI: 10.1038/s41598-017-07501-4
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility explains preferred thiol-disulfide isomerization in a protein domain

Abstract: Disulfide bonds are key stabilizing and yet potentially labile cross-links in proteins. While spontaneous disulfide rearrangement through thiol-disulfide exchange is increasingly recognized to play an important physiological role, its molecular determinants are still largely unknown. Here, we used a novel hybrid Monte Carlo and Molecular Dynamics scheme to elucidate the molecular principles of thiol-disulfide exchange in proteins, for a mutated immunoglobulin domain as a model system. Unexpectedly, using simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 53 publications
1
37
0
Order By: Relevance
“…Achieving a native disulfide pattern during folding, for proteins that contain more than two cysteine residues, often involves the reduction and rearrangement of non-native disulfide bonds. These must be surface-exposed in order to be accessible to attacking thiols during isomerisation [ 73 , 74 ]. It is well established that reducing PDIs act on released substrates in the ER; however, can they also act on substrates at the co-translational stage?…”
Section: The Role Of Pdi Family Members In Nascent Polypeptide Folmentioning
confidence: 99%
“…Achieving a native disulfide pattern during folding, for proteins that contain more than two cysteine residues, often involves the reduction and rearrangement of non-native disulfide bonds. These must be surface-exposed in order to be accessible to attacking thiols during isomerisation [ 73 , 74 ]. It is well established that reducing PDIs act on released substrates in the ER; however, can they also act on substrates at the co-translational stage?…”
Section: The Role Of Pdi Family Members In Nascent Polypeptide Folmentioning
confidence: 99%
“…However, only in 2007, with the development of the exciting single-molecule techniques, were Julio Fernandez and co-workers (Wiita et al, 2006;Alegre-Cebollada et al, 2010), able to study the force-dependent chemical kinetics of the disulfide bond reduction, reporting a value of 0.34 Å, for the distance to the transition state of the reaction, in perfect agreement with Fernandes and Ramos work of 2004 (Fernandes and Ramos, 2004). More recently, Kolšek and co-workers suggested that thiol-disulfide exchange in protein folding often relies on simple accessibility criteria between thiolates (Kolsek et al, 2017).…”
Section: Introductionmentioning
confidence: 60%
“…Recent evidences suggest that disulphide bonds in proteins are highly dynamic (reviewed in [ 34 ]). Disulphide bonds may react with thiols within proteins even in the absence of enzymes and re-shuffle spontaneously or on an external stimulus, inducing changes in protein conformation and possibly function [ 3 , 22 ]. To examine this possibility, we performed homology modeling search for possible candidate cysteines.…”
Section: Resultsmentioning
confidence: 99%